Differences in metabolic characteristics between Metabolically Healthy Obesity (MHO) and Metabolically Unhealthy Obesity (MUO) in weight reduction therapy - Shiori Kawai; Hajime Yamakage; Kazuhiko Kotani; Mitsuhiko Noda; Noriko Satoh-Asahara; Koshi Hashimoto (Endocrine Journal)
Metabolically Healthy Obesity (MHO) is generally recognized as the absence of any metabolic disorders and cardiovascular diseases, including type 2 diabetes, dyslipidemia, and hypertension, in obese individuals; however, it is not clearly defined. Therefore, the present study investigated differences in metabolic characteristics between individuals with MHO and Metabolically Unhealthy Obesity (MUO) during weight reduction therapy. The key factors defining MHO and the importance of weight reduction therapy for MHO were also examined. Cohort data from the Japan Obesity and Metabolic Syndrome (JOMS) study were analyzed. Subjects were divided into the MHO (n = 25) and MUO (n = 120) groups. Prior to weight reduction therapy, serum adiponectin levels were significantly higher in the MHO group than in the MUO group. Serum adiponectin levels also negatively correlated with the area of subcutaneous adipose tissue (SAT) and Homeostasis model assessment (HOMA)-R in the MHO group, but not in the MUO group. Collectively, the present results suggest the importance of adiponectin for maintaining metabolic homeostasis in the MHO group. On the other hand, no significant differences were observed in inflammatory markers between the MHO and MUO groups, suggesting the presence of chronic inflammation in both groups. Furthermore, a positive correlation was noted between changes in serum cystatin C levels and waist circumference in the MHO group, which indicated that despite the absence of metabolic disorders, the MHO group exhibited anti-inflammatory responses during weight reduction therapy. These results underscore the significance of weight reduction even for individuals with MHO.